ACE2 and TMPRSS2 polymorphisms in various diseases with special reference to its impact on COVID-19 disease. (January 2021) - Singh, HariOm; Choudhari, Ranjana; Nema, Vijay; Khan, Abdul Arif
Abstract: Background: A carboxypeptidase protein called ACE2 is found in many organs. ACE2 protein can play a pivotal role to regulate the pathological changes of several diseases including COVID-19. TMPRSS2 gene is expressed in many human tissues and plays a critical role in spreading the infection of the viruses including coronavirus and progression of prostate cancer, and hence could be used as a potential drug target. There are limited reports on occurrence of genetic polymorphism of ACE2 and TMPRSS2 in general population, expressions in pathological conditions, and its impact on COVID-19 disease. Hence we comprehended the occurrence of ACE2, TMPRSS2 polymorphism in general population, expression in various diseases and its impact on COVID-19 disease. Method: We utilized multiple databases, PubMed (Medline), EMBASE and Google Scholar for literature search. Description: ACE2 polymorphisms have significant linkages with various diseases, including severity of SARS-CoV-2 infection. Genetic variations of these genes contribute to individual's genetic susceptibility to viral infection and its subsequent clearance. The diversity and variations in the population distribution of these genes, might greatly influence and in turn reflect into the observed population and gender differences of the severity and clinical outcomes of SARS-CoV-2 infection. Conclusion: There are diversities in distribution of ACE2 and TMPRSS2 polymorphisms among different populations. Analyzing the genetic variants and expression of ACE2 and TMPRSS2 genes, in a population may provide the genetic marker for susceptibility or resistance against the coronavirus infection, which might be useful for identifying the susceptible population groups for targeted interventions and for making relevant public health policy decisions. Graphical abstract: Image 1 Highlights: Analyzing the expression of cellular genes may provide the genetic marker for susceptibility to coronavirus infection. Analyzing the polymorphism of ACE2 and TMPRSS2 genes would be helpful to forecast the clinical outcomes of COVID-19 disease. Analyzing the TMPRSS2 rs35074065 polymorphism among SARS-CoV-2 infected populations could predict the genetic susceptibility.